Aplicaciones Clínicas del Modelo Dinámico-Maduracional de Apego y Adaptación: Evaluación, Formulación y Principios de Atención - Baim, Clark (Revista de Psicoterapia, 2025)
Earlier in this journal issue, I offered an introduction to Dr Patricia M. Crittenden’s Dynamic-Maturational Model (DMM) of Attachment and Adaptation. The DMM is a bio-psycho-social model, informed by neurodevelopmental research, and as such it offers a developmental understanding of the wide range of adaptations used by people who are endangered or endangering to others, or who may need psychological or social care support for a wide variety of reasons. The DMM is a strengths-based, non-labelling and non-pathologising model which conceptualises adaptations to danger as self-protective strategies that promote survival in their original context, but which may later lead to problematic, dangerous or self-defeating behaviour. This article focuses on the clinical applications of the DMM, which includes DMM-informed principles of assessment, formulation and care.